KBG syndrome: report and follow-up on three unrelated patients observed at different ages - Gregorio Serra; Pierandrea Elefante; Ylenia Gazzitano; Luigi Memo; Valeria Mineo; Carla Morando; Rosaria Nardello; Ettore Piro; Laura Travan; Giovanni Corsello (Italian Journal of Pediatrics, 2025)
Abstract Background KBG syndrome (MIM #148050) is a rare genetic disease, showing an autosomal dominant pattern of inheritance. It was first described by Herrmann et al. in 1975 in three affected families, whose initial letters gave origin to the acronym. A peculiar facies including triangular face, synophrys, macrodontia of the upper central incisors, as well as short stature, skeletal defects and neurodevelopmental disorders (developmental delay, intellectual disability, epilepsy) are the main features of the syndrome. Mutations of the ankirin repeat domain 11 gene (ANKRD11), which harbors at chromosome 16q24.3, have been associated to the syndrome. The encoded protein inhibits ligand-dependent activation of transcription. Due to the growing number of detected ANKRD11 variants associated to phenotypes with various degree of severity, the precise definition of the clinical and genomic profiles of patients is important, also in the perspective of a better understanding of the molecular bases of the disease, genotype-phenotype correlation, and management of affected subjects. Cases presentation We report on three unrelated patients, observed in as many different Italian (Sicily, Veneto and Friuli-Venezia-Giulia regions) Pediatric Neurology and Medical Genetics outpatient services, showing variously present typical dysmorphic features (e.g., triangular face, macrodontia of upper incisors, brachydactyly), growth retardation and impaired neurodevelopmental profiles (i.e. developmental delay, EEG abnormalities/epilepsy) compatible with KBG syndrome diagnosis. In Patient 1, next generation sequencing analysis of a panel of genes involved in developmental delay and autism spectrum disorders detected two mutations, a pathogenic heterozygous frameshift variant of the ANKRD11 gene (already described in the literature), and a heterozygous missense one in EHMT1 (previously reported as well, and associated with Kleefstra syndrome); in Patient 2, array comparative genomic hybridization (a-CGH) analysis identified a 634 Kb 16q24.3-24.3 deletion involving several genes (CDT1, APRT, GALNS, TRAPPC2L, ACSF3, CDH15), besides ANKRD11, some of which are related with developmental disorders. Finally in Patient 3, Sanger sequencing of the ANKRD11 gene, performed due to the specific diagnostic suspicion raised for precocious teething observed at age 3 months, evidenced an intragenic deletion allowing thus an early diagnosis of disease. Conclusions We underline similarities and differences among our patients, and their specific genetic and clinical features, in addition to the variable diagnostic tests used for the diagnosis, reached at different developmental age, i.e. infancy, childhood and adolescence. Pediatricians must be aware of KBG syndrome and should be able, as well, to raise the diagnostic suspicion, especially in the presence of peculiar dysmorphic features, short stature, developmental delay, intellectual disability and epilepsy. Prompt diagnosis may allow to better address any associated emerging neuropsychological and behavioral issues improving the quality of life of the patient and the whole family.